“Fostering Creativity and Artistic Competencies through Visual Arts Education in Schools and Universities” - Aslonova Shaxnoza Islom qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article explores the role of visual arts in fostering creativity and artistic competencies in students across school and higher education levels. It emphasizes how early exposure to visual arts supports cognitive, aesthetic, and creative development, and how higher education further strengthens these skills through complex projects and independent work. The study highlights the importance of integrating visual arts in curricula to promote holistic student development and prepare them for professional artistic careers.